Integrate or perish : perspectives of the Heads of Government of the Caribbean Community and Commonwealth Caribbean countries 1963-2002 - Hall, Kenneth O. (Ian Randle Pub. KingstonJM, 2003)
Chronicles the challenges faced by the Integration Movement over the last thirty years and its capacity for recovery and sustained development. Traces the growth, development, setbacks and survival of the Movement. Includes the speeches by Caribbean Heads of Government up to 2002.